Two novel mutations in the DNAH11 gene in primary ciliary dyskinesia (CILD7) with considerable variety in the clinical and beating cilia phenotype - Rüdiger Schultz; Varpu Elenius; Heikki Lukkarinen; Tanja Saarela (BMC, 2022)
Background Diagnosis of primary ciliary dyskinesia (PCD) still remains a challenge, especially with mutations in the Dynein Arm Heavy Chain 11 (DNAH11) gene. Classical diagnostic measures like Transmission Electron Microscopy (TEM) are not applicable for mutations in the DNAH11 gene since ultrastructural defects of the ciliary apparatus are absent. Novel mutations encoding for PCD appear all the time with considerable variation in the clinical picture, making it necessary to update data bases and guidelines for PCD diagnostics. Methods In this study we examined two unrelated, Finnish families with symptoms of PCD applying the clinical scoring system: Primary ciliary dyskinesia Rule (PICADAR), high speed video microscopy analysis (HSVMA) for ciliary movement, a commercially available gene panel analysis and nasal Nitric Oxide (nNO) measurements if applicable. Results Two, likely pathogenic variants in the DNAH11 gene (c.2341G > A, p. (Glu781Lys) ja c.7645 + 5G > A) were detected. In the first family, compound heterozygous mutations led to disease manifestation in two of 4 children, which showed a similar phenotype of cilia beating pattern but marked differences in disease severity. In the second family, all three children were homozygotes for the c.2341G > A p.(Glu781Lys) mutation and showed a similar degree of disease severity. However, the phenotype of cilia beating pattern was different ranging from stiff, static cilia to a hyperkinetic movement in one of these children. Conclusions In this study we describe two Finnish families with PCD, revealing two novel mutations in the DNAH11 gene which show considerable variety in the clinical and beating cilia phenotype. The results of this study show the clinician that PCD can be much milder than generally expected and diagnosis demands a combination of measures which are only successful in experienced hands. Chronic and repeatedly treated wet cough should raise suspicion of PCD, referring the patient for further diagnostics to a specialised PCD centre.